HUBUNGAN ASPEK ADMINISTRASI, KODING, DAN DOKUMEN MEDIS DENGAN KELENGKAPAN KLAIM BPJS KESEHATAN PASIEN RAWAT JALAN DI RSD IDAMAN BANJARBARU - siti tanzilah; Melinda Restu Pertiwi; Zubaidah Zubaidah; Rusdiana Rusdiana (Journal of Hospital Administration and Management (JHAM), 2026)
Hospital claims are reimbursement submissions for healthcare services provided to National Health Insurance (JKN) participants administered by BPJS Kesehatan. Incomplete or inaccurate claim documents may result in Pending claim status, leading to delays in payment to healthcare facilities. This study aimed to determine the relationship between administrative aspects, coding processes, and medical documents with the completeness of BPJS Kesehatan outpatient claims at RSD Idaman Banjarbaru. This research employed a quantitative method with a cross-sectional approach. The research instrument consisted of a checklist sheet for claim document completeness. The study population included all outpatient claim submission files for the period of July–September 2025, totaling 386 files. The sample comprised 196 files selected using purposive sampling techniques based on predetermined inclusion and exclusion criteria. Data analysis was conducted through univariate and bivariate approaches using the chi-square test. The statistical analysis results demonstrated significant relationships between administrative aspects, coding processes, and medical documents with the completeness of BPJS Kesehatan outpatient claims, as indicated by a p-value of 0.001 (p < 0.05). It can therefore be concluded that improving administrative accuracy, coding precision, and the completeness of medical documents is essential to minimize incomplete claims and prevent Pending claim status. It is recommended to strengthen coordination among coding staff, physicians, and verifiers to improve claim accuracy, as well as to implement double-check procedures for coding before claim submission. In addition, continuous training programs and routine internal audits are necessary to identify and address the causes of claim discrepancies.